Zombie Company and CSR Performance with Corporate Governance and Ownership as Moderator Variables - Muhammad Madyan; Nugroho Sasikirono; Putri Maulidya (Riset Akuntansi dan Keuangan Indonesia)
This study aims to determine the relationship between zombie companies and the performance of corporate social responsibility, with corporate governance and ownership as moderator variables. A zombie company is a nearinsolvent firm due to inefficiency and low profitability but still survive with external support from the government or bank (Kane, 1987). The determination of the sample is done by a purposive sampling method, with OLS and Moderated Regression Analysis methods. The number of research samples is 288 companies with a total of 1865 observations for the period 2010-2017. The analysis shows that CSR performance in zombie companies is lower than that of nonzombies. The moderator variable of corporate governance is proxied by board composition, while ownership is proxied by family ownership and institutional ownership. The board composition and institutional ownership variables do not moderate the negative effects of zombie companies on CSR performance, while the family ownership variable worsens the relationship between zombie companies and CSR performance. The research control variables are financial leverage, a dummy of state-owned enterprise, and firm size. While financial leverage has no effect on the CSR performance, the state-owned enterprise and firm size are positively related to that performance.